Knowledge sharing behaviour, leadership style, human capital and job performance of academicians’: Moderating role of entrepreneurial orientation - Siam, Ibrahim Mahmoud Ibrahim (2021)
In recent years, higher education in developing countries such as Jordan has undergone rapid changes. In order to meet those changes, academicians’ high performance is required to initiate this transformation process and academicians have a very important role to play. This study examined the relationship between knowledge-sharing behaviour, transformation leadership, transactional leadership, and human capital towards academicians’ job performance. It also investigated the moderating effect of entrepreneurial orientation (EO) on the relationship. This study integrated different theories such as the resource-based view theory and the complementary assets theory with the purpose to map and position the possible relationships between the variables in the conceptual framework. Besides, the research used the quantitative approach to study the relationship between the variables, and the unit of analysis was the individual academic staff. By using the proportionate stratified random sampling technique, 1,000 questionnaires were distributed by approaching the academicians from nine public universities in Jordan. Out of the 1,000 questionnaires distributed, 418 questionnaires were returned, representing a response rate of 41.8%. However, only 395 of the questionnaires were used for further analysis. Hypotheses regarding the direct effects and the moderating effects were tested using the Smart PLS 2.0. Results of the direct effects showed that knowledge-sharing behaviour, leadership (transactional and transformational), and human capital had positive relationships with the job performance of academicians. EO was found to moderate the relationship between knowledge-sharing behaviour, transactional leadership and human capital. However, EO did not moderate the relationship between transformational leadership and job performance of academicians. Based on the results obtained, theoretical and practical implications, limitations and suggestions for future research are discussed and highlighted.